Deiksis Persona pada Pronomina Persona dalam Anime Barakamon Karya Tachibana Masaki - Rian Meriandini, I Gusti Ayu; Dian Aryani, Made Ratna; Budiana, I Made (Humanis; Vol 23 No 3 (2019)DO - 10.24843/JH.2019.v23.i03.p11, 2019)
The title of this research is “Personal Deixis on Personal Pronoun of Barakamon Anime Created by Tachibana Masaki” that aimed to research the deixis form, deixis reference, and deictic shift on personal pronoun of Barakamon anime 1-12 episode created by Tachibana Masaki. This research was analyzed by using descriptive method and informal technique. Deixis form and deixis reference analysis used personal deixis of pragmatic theory by Yule (1996) and personal deixis reference by Halliday and Hasan (1976). While the deictic shift analysis used personal deictic shift theory by Purwo (1984). The result of this research is on Barakamon anime was found three types of person deixis in the personal pronoun with each type of person deixis divided into two forms are singular and plural i.e. first personal deixis e.g. watashi, atashi, boku, ore, uchi, watashitachi, watashira, atashira, bokutachi, bokura, oretachi, orera, uchira, and wareware, second personal deixis e.g. anata, anta, kimi, omae, anatatachi, antatachi, antara, omaetachi, and omaera, and third personal deixis e.g. kare, koitsu, soitsu, aitsu, koitsura and aitsura. Deixis reference that found are exophora reference and endophora reference with anaphora category. And deictic shift that found are personal deictic shifting first personal form for second personal by using watashi, personal deictic shifting second personal form for first personal by using omae and omaera, and personal deictic shifting second personal form for third personal by using anata and omae.